REPRESENTATION OF SOCIAL CLASSS IN THE SHORT STORY THE NECKLACE - Alia, Regina Putri; Nurholis, Nurholis (Jurusan Sastra Indonesia, 2024)
The objective of this study is to examine Guy de Maupassant's short story,